PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PNS DENGAN KOMPENSASI SEBAGAI PEMODERASI - Miswanto Miswanto; Rr. Niken Purwasari; Isnanda Zainur Rohman (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
This study aims to test whether: 1) leadership style and work discipline have influence on the performance of civil servants, 2) compensation moderates the influence of leadership style on the performance of civil servants, and 3) compensation moderates the effect of work discipline on the performance of civil servants. This research was conducted in November 2019 and completed in January 2020 in three Sub-Districts: Tegalrejo, Gedongtengen, and Danurejan, Yoyakarta City. Research respondents are civil servants in the region. Sampling is done by non-probability sampling with purposive sampling. The number of samples is 100 respondents. The data used are primary data using a questionnaire instrument. Hypothesis testing uses linear multiple regression models and moderated regression analysis (MRA). The research instrument used is valid and reliable. The data processed passed the classical assumption test. The findings of this study are as follows. Leadership style and work discipline have a positive effect on the performance of civil servants. Compensation moderates the effect leadership style on the performance of civil servants, and the moderation reinforces. However, compensation does not moderate the effect of work discipline on the performance of civil servants. Penelitian ini bertujuan untuk menguji apakah: 1) gaya kepemimpinan dan disiplin kerja mempunyai pengaruh terhadap kinerja PNS, 2) kompensasi memoderasi pengaruh gaya kepemimpinan terhadap kinerja PNS, dan 3) kompensasi memoderasi pengaruh disiplin kerja terhadap kinerja PNS. Penelitian ini dilakukan bulan November 2019 dan selesai Januari 2020 pada tiga wilayah pemerintahan Kecamatan Tegalrejo, Gedongtengen, dan Danurejan, Kota Yoyakarta. Responden penelitian adalah PNS di wilayah tersebut. Sampel dipilih dengan non-probability sampling melalui purposive sampling. Jumlah sampel sebanyak 100 responden. Data yang diolah adalah data primer yang diperoleh dari penyebaran kuesioner kepada responden. Pengujian hipotesis dengan menggunakan model regresi berganda linear dan moderated regression analysis (MRA). Instrument penelitian ini mengindikasikan valid dan reliable. Data yang diolah lulus uji asumsi klasik.Temuan penelitian ini seperti berikut. Gaya kepemimpinan dan disiplin kerja mempunyai pengaruh positif terhadap kinerja PNS. Kompensasi memoderasi memperkuat pengaruh gaya kepemimpinan terhadap kinerja PNS. Akan tetapi, kompensasi tidak memoderasi pengaruh disiplin kerja terhadap kinerja PNS.